Lasallian awards were conferred on La Salle alumni who have brought honor and distinction to DLSU and to the country - Lim, Patricio H. (Animo Repository, 1999)
The Distinguished Lasallian Awards were conferred on La Salle alumni who have brought honor and distinction to DLSU and to the country during the La Salle Class '74 alumni homecoming and reunion. The honorees were: Msgr. Patricio H. Lim (GS '44, HS '49, BSC '53), Jose M. Reyes (HS '49), and Jorge W. Jose (HS '34, Associate of Science in Commerce '36, BSC '37).